Bacterial secretant from Pseudomonas aeruginosa Dampens inflammasome activation in a Quorum sensing-Dependent Manner - Yang, Jungmin; Lee, Kang-Mu; Park, Sangjun; Cho, Yoeseph; Lee, Eunju; Park, Jong-Hwan; Shin, Ok Sarah; Son, Junghyun; Yoon, Sang Sun; Yu, Je-Wook (FRONTIERS MEDIA SA, 2017)
Inflammasome signaling can contribute to host innate immune defense against bacterial pathogens such as Pseudomonas aeruginosa. However, bacterial evasion of host inflammasome activation is still poorly elucidated. Quorum sensing (QS) is a bacterial communication mechanism that promotes coordinated adaptation by triggering expression of a wide range of genes. QS is thought to strongly contribute to the virulence of P. aeruginosa, but the molecular impact of bacterial QS on host inflammasome defense is completely unknown. Here, we present evidence that QS-related factors of the bacterial secretant (BS) from P. aeruginosa can dampen host inflammasome signaling in mouse bone marrow-derived macrophages. We found that BS from QS-defective Delta lasR/rhlR mutant, but not from wild-type (WT) P. aeruginosa, induces robust activation of the NLRC4 inflammasome. P. aeruginosa-released flagellin mediates this inflammasome activation by Delta lasR/rhlR secretant, but QS-regulated bacterial proteases in the WT BS impair extracellular flagellin to attenuate NLRC4 inflammasome activation. P. aeruginosasecreted proteases also degrade inflammasome components in the extracellular space to inhibit the propagation of inflammasome-mediated responses. Furthermore, QS-regulated virulence factor pyocyanin and QS autoinducer 3-oxo-C12-homoserine lactone directly suppressed NLRC4-and even NLRP3-mediated inflammasome assembly and activation. Taken together, our data indicate that QS system of P. aeruginosa facilitates bacteria to evade host inflammasome-dependent sensing machinery.
Keywords: CYSTIC-FIBROSIS; IMMUNE RECOGNITION; NLRC4 INFLAMMASOME; AIM2 INFLAMMASOME; LUNG INFECTION; HOST DEFENSES; CASPASE-1; PYOCYANIN; FLAGELLIN; IPAF